Industry 4.0 and Cyber Security Issues and Challenges - et. al., Mamoona Humayun, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the current era of technology, by exploiting the vulnerabilities of networked production equipment, a growing number of cybersecurity breaches have adversely affected business efficiency especially in the context of Industry 4.0. Or Industrial internet of things (IIoT). Cyber-attacks on sensitive industrial equipment may disrupt the corporate business model in some cases. Therefore, there is a need to provide an awareness to the industry 4.0 practitioners about the layered architecture of Industry 4.0 along with possible attacks targeting these layers. Further, the consequences of these attacks along with countermeasures will provide a better overview of the situation. It will also help Industry 4.0 practitioners in better management of the cyber physical system. To do this, this paper provides a detailed overview of possible cyber-attacks targeting each layer of industry 4.0 along with the consequences of these attacks and corresponding countermeasures. Further, a layered framework is provided as a contribution to research that will provide end-to-end protection from existing cyber-attacks.